ANALISIS PENERAPAN DIFFSERV PADA TEKNOLOGI TCP/IP TRADISIONAL UNTUK JARINGAN PERANGKAT TELEKOMUNIKASI 3G BERBASIS IP DI PT INDOSAT, TBK. CABANG MALANG - Winarko Putro, Okma (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2013)
The third generation mobile communication technology or 3G allows users to enjoy various high-speed communications services. PT Indosat, Tbk. as one of the leading mobile operators in Indonesia builds IP-based 3G telecommunications network in Malang, which consists of 3G cellular network transmitters (Node B) and Radio Network Controller (RNC), over an IP/MPLS network that become the communication line among 3G telecommunication network elements. Network devices with traditional TCP/IP concept, which is the beginning of IP/MPLS development, has a lower implementation cost and a feature to implement DiffServ (Differentiated Services) to improve Qualiy of Service (QoS). The goal of this research is to design and build a small-scale traditional TCP/IP network (testbed) and performing analysis on the Diffserv implementation. The analysis shows that DiffServ can be applied to the designed network and able to improve QoS by making priorites based on Differentiated Service Code Point (DSCP). The testbed network is Â also capable of handling 3 Node B which is connected to 1 RNC.Â Key words: Diffserv, QoS, TCP/IP, 3G